2018
DOI: 10.1177/2325967118779786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of an Arthroscopic Knotless Suprapectoral Biceps Tenodesis Technique: Loop ’n’ Tack Tenodesis

Abstract: Background:Pathology of the long head of the biceps tendon is a well-known cause of shoulder pain that is commonly managed with arthroscopic suprapectoral biceps tenodesis when conservative treatment fails.Purpose:To present an arthroscopic knotless suprapectoral biceps tenodesis technique known as “Loop ’n’ Tack” tenodesis and to report the clinical outcomes of patients with a minimum 2 years of follow-up.Study Design:Case series; Level of evidence, 4.Methods:A retrospective review of all patients who had und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…These results indicate that the biomechanics of the Loop ’n’ Tack technique as at least equivalent to commonly used techniques in terms of failure strength and demonstrate that it is a viable option for tenodesis surgery, especially in the proximal biceps. Prior work by Brady et al 2 and Duerr et al 3 has shown that suprapectoral proximal biceps tenodesis is an acceptable treatment option with acceptable outcomes, and we believe our work adds to the validity of the proximal tenodesis while potentially limiting its downside. A retrospective analysis of the Loop ’n’ Tack proximal biceps tenodesis technique demonstrated high patient satisfaction and shoulder outcome scores with minimal postoperative complications.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These results indicate that the biomechanics of the Loop ’n’ Tack technique as at least equivalent to commonly used techniques in terms of failure strength and demonstrate that it is a viable option for tenodesis surgery, especially in the proximal biceps. Prior work by Brady et al 2 and Duerr et al 3 has shown that suprapectoral proximal biceps tenodesis is an acceptable treatment option with acceptable outcomes, and we believe our work adds to the validity of the proximal tenodesis while potentially limiting its downside. A retrospective analysis of the Loop ’n’ Tack proximal biceps tenodesis technique demonstrated high patient satisfaction and shoulder outcome scores with minimal postoperative complications.…”
Section: Discussionmentioning
confidence: 60%
“…A retrospective analysis of the Loop 'n' Tack proximal biceps tenodesis technique demonstrated high patient satisfaction and shoulder outcome scores with minimal postoperative complications. 3…”
Section: Discussionmentioning
confidence: 99%
“…1,12,13,18,33 Although open techniques tended to have higher rates of morbidity, including nerve injury and wound complications, no study detected a clinically significant difference between the 2 techniques. 1,12,13,18,33 Duerr et al 10 reported an increase in ASES scores from 42.6 preoperatively to 91.0 postoperatively with their described arthroscopic suprapectoral biceps tenodesis. Our results are similar to these previous studies in that those patients undergoing our allarthroscopic technique had satisfactory clinical results with no complications at an average of 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, 1 This technique has been highly successful. Although I have converted to the onlay "loop 'n' tack" technique, 5 I still perform this technique high in the groove. I frequently use the sutures emanating from this tenodesis site for additional repairs, including upper subscapularis or anterior supraspinatus repairs.…”
Section: See Related Article On Page 2975mentioning
confidence: 99%